In vitro Plant Regeneration of Magnolia punduana: An Endemic and Threatened Plant Species (Plant Tissue Culture and Biotechnology, 2017)
Shoots were induced from axillary and nodal buds of Magnolia punduna on MS supplemented with 0.1 μm of BAP. Out of five basal media tested (MS, ½ MS, ¼ MS, LS and WP), MS was found to be most effective for shoot and callus initiation. Different plant growth regulators (0.1 ‐ 1.0 μm) induced shoot formation in different proportions. The combination of 0.1 μm IBA and 0.5 μm BAP was found optimum for shoot elongation with minimal necrosis of the explants. Half strength of MS supplemented with 8.0 μm IBA was found suitable for rooting.Plant Tissue Cult. & Biotech. 27(2): 153-159, 2017 (December)